Experimental investigation of AQSOA-Z02 zeolite-water based adsorption chiller - Chua, Pei Ling (2015)
With environmentalism on the move in recent years, many private organisations and government bodies have begun to turn to green technology as a sustainable goal for the long run. Inevitably, adsorption cooling started to gain considerable interest of major players in the refrigeration industry simply because of its environmentally-benign nature. Besides, adsorption cooling can be operated with low grade waste heat recovered from industrial processes or even renewable solar energy, or a co-regeneration plant. Yet, adsorption refrigeration system fails to overtake the position of the popular vapour compression cycle due to the former's substantially lower coefficient of performance and bulky in size. Foreseeing the potential behind this technology, many researchers have embarked on numerous studies and investigations to further enhance the efficiency of adsorption cycle, and also reduce the size of the adsorption reactor. Not long ago, Mitsubishi introduced a new series of promising zeolites AQSOA adsorption cooling equipment which were found to have larger working capacity than conventional silica gel equipment at low regeneration temperatures. Following a 'S' shaped isotherm, AQSOA-Z02 in specific undergoes monolayer (or multi-layers) of adsorption stage at low partial pressure and micropore filling within the zeolite pores at higher partial pressure. Thus, to examine the performance AQSOA-Z02 in adsorption chiller applications, experimental investigation was carried out for this project. Experiments were carried out with a 10 kW, Z02-water based adsorption chiller. The parametric analysis, varying the hot water inlet temperature and flow rate was reported. Key performance parameters namely coefficient of performance (COP) and cooling capacity were used to evaluate the adsorption cycle. Indeed, excellent chilling was observed with chilled water outlet temperature reaching nearly 10oC even at low hot water inlet temperatures. At 60oC hot water inlet temperature, the cycle generates 3.2 kW of cooling and achieves relatively high COP of 0.488 experimentally.